2000
DOI: 10.1046/j.1365-2494.2000.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte effects on reproduction of a root‐knot nematode (Meloidogyne marylandi) and osmotic adjustment in tall fescue

Abstract: In a 2 × 2 × 2 factorial experiment, plants of one genotype of tall fescue (Festuca arundinacea) were grown in soil in pots in a glasshouse on two occasions. The treatments were either with (E+) or without (E–) infection by the fungal endophyte Neotyphodium coenophialum; with (N+) or without (N–) inoculation by the root‐knot nematode Meloidogyne marylandi; and with or without water deficit stress. In the first experiment, nematode numbers after 5 weeks had increased 10 times in the E–/N– watered pots and 22 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…Endophytes can also have additional beneficial properties, such as accelerating seedling emergence, promoting plant growth and tolerance to adverse conditions (Harman, 2011;Companta et al, 2010). Fungal endophytes are quite common in nature and several roles have been recognised, including providing protection against herbivorous insects, plant parasitic nematodes (Elmi et al, 2000), and plant pathogens (Dingle and McGee, 2003;Wicklow et al, 2005). It has been shown that endophytic B. bassiana is compatible with both Bt and carbofuran applications used to suppress Ostrinia nubilalis .…”
Section: Endophytesmentioning
confidence: 99%
“…Endophytes can also have additional beneficial properties, such as accelerating seedling emergence, promoting plant growth and tolerance to adverse conditions (Harman, 2011;Companta et al, 2010). Fungal endophytes are quite common in nature and several roles have been recognised, including providing protection against herbivorous insects, plant parasitic nematodes (Elmi et al, 2000), and plant pathogens (Dingle and McGee, 2003;Wicklow et al, 2005). It has been shown that endophytic B. bassiana is compatible with both Bt and carbofuran applications used to suppress Ostrinia nubilalis .…”
Section: Endophytesmentioning
confidence: 99%
“…Comparison of a transgenic nonergot alkaloidproducing strain (deletion of the dmaW gene encoding the first step of ergot alkaloid production) to the wild type strain showed endophyte-associated suppression of P. scribneri in perennial ryegrass was still evident suggesting other mechanisms might be responsible for the suppression (Panaccione et al, 2006). Reduction in root-knot nematode (Meloidogyne marylandi) population densities by ergot alkaloid-producing endophyte infected tall fescue plants has also been reported (Elmi et al, 1999). Each of these studies was conducted with summer-active tall fescue cultivars (Timper et al, 2005;Bacetty et al, 2009) or perennial ryegrass (Panaccione et al, 2006) and may not translate to effects seen with summer-dormant varieties.…”
mentioning
confidence: 95%
“…Fungal endophytes have been detected in hundreds of plants, including many important agricultural commodities such as wheat (Larran et al, 2002a), bananas (Pocasangre et al, 2000;Cao et al, 2002), soybeans (Larran et al, 2002b), and tomatoes (Larran et al, 2001). Several roles have been ascribed to fungal endophytes, including providing protection against herbivorous insects (Breen, 1994;Clement et al, 1994), plant parasitic nematodes (West et al, 1988;Elmi et al, 2000), and plant pathogens (White and Cole, 1986;Dingle and McGee, 2003;Wicklow et al, 2005).…”
Section: Introductionmentioning
confidence: 99%